Isolation of Pasteurella haemolytica from the Spleen of Chickens - Majid, M. Shah; Ideris, Aini; Aziz, A. Rahman (1986)
Pasteurella haemolytica was isolated from eight spleens of chickens with white focal lesions. A pathogenicity study in chickens did not reveal any significant findings.